Improving the preparation of the investigative interviewing of suspects: A multidisciplinary perspective - Luknar, Ivana; Bull , Ray; Stanojević, Petar (Sociološki pregled, 2024)
Building and improving investigative interviewing standards is an important topic for police, citizens and finally society. This paper attempts to improve police interviewing of suspects. We further develop the concept of investigative interviewing by linking it to important insights by social movement scholars. Differences in theories reflect different approaches to the interviewing of suspects. In this article, we explore a variety of theories that may improve preparation for the interviewing of suspects. We provide a multidimensional quality and import theories from sociology, psychology and behavioural studies, modifying these to better fit the investigative interviewing of suspects. The main method applied in the paper is content analysis. The article and its conclusions also address the broader implications of understanding the importance of planning for the investigative interviewing of suspects. Results of the study indicate need for actively seeking of best practices of the investigative interviewing of suspects. Understanding what motivates person to commit a crime is also a crucial aspect of police investigation. Findings of the study may serve as impulse for evaluation and improvement of existing practices of interviewing of suspects and contribute to the broader knowledge in this area. The aforementioned represents a good basis for the development of simulation models for the training of investigators.